Catalyzing Scientific Innovation with Design Thinking. (23rd July 2015) - Yajima, Rieko
<x xml:space="preserve">Abstract</x> The scientific community plays a critical role in helping to solve grand challenges that affect society, while facing budget reductions and other pressures. Can design thinking offer ways to accelerate and further innovation in scientific research and discovery? Designers and scientists have a lot in common—the desire to understand the world around them, the passion to discover something unexpected, and the ability to look at the world in a new way. Can we talk?